Is Remuneration a Hygiene Factor in Higher Education? Evidence from ICT Competence, Prophetic Leadership, and Lecturer Performance in Indonesian Public Service Agency Universities - Khaeroni Khaeroni; Ilzamudin Ilzamudin; Subhan Subhan (Management of Education: Jurnal Manajemen Pendidikan Islam, 2026)
Despite extensive remuneration reforms in Indonesian Public Service Agency universities (PTN BLU), empirical evidence remains inconclusive as to whether financial incentives genuinely improve lecturer performance. Most prior studies emphasize satisfaction effects, leaving a gap regarding remuneration’s role as a performance driver once adequacy thresholds are met. Grounded in Herzberg’s Two-Factor Theory and supported by the MARS Model, this study positions remuneration as a potential hygiene factor, ICT competence as an ability dimension, and prophetic leadership as a value-based determinant shaping role perceptions. A quantitative cross-sectional survey of 390 permanent lecturers was analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal that remuneration has no significant direct effect on lecturer performance once perceived as adequate. In contrast, ICT competence exerts a strong positive influence (p < 0.001), and prophetic leadership shows a moderately significant effect (p < 0.001). The model explains 72.3% of the variance in performance. This study provides original empirical evidence that remuneration primarily functions as a hygiene factor in Islamic public higher education, highlighting the strategic importance of digital competence and value-based leadership beyond financial incentives.